Geographic Variation in Larval Metabolic Rate Between Northern and Southern Populations of the Invasive Gypsy Moth. Issue 4 (11th July 2018) - May, Carolyn; Hillerbrand, Noah; Thompson, Lily M; Faske, Trevor M; Martinez, Eloy; Parry, Dylan; Agosta, Salvatore J; Grayson, Kristine L
Abstract: Thermal regimes can diverge considerably across the geographic range of a species, and accordingly, populations can vary in their response to changing environmental conditions. Both local adaptation and acclimatization are important mechanisms for ectotherms to maintain homeostasis as environments become thermally stressful, which organisms often experience at their geographic range limits. The spatial spread of the gypsy moth ( Lymantria dispar L.) (Lepidoptera: Erebidae) after introduction to North America provides an exemplary system for studying population variation in physiological traits given the gradient of climates encompassed by its current invasive range. This study quantifies differences in resting metabolic rate (RMR) across temperature for four populations of gypsy moth, two from the northern and two from southern regions of their introduced range in North America. Gypsy moth larvae were reared at high and low thermal regimes, and then metabolic activity was monitored at four temperatures using stop-flow respirometry to test for an acclimation response. For all populations, there was a significant increase in RMR as respirometry test temperature increased. Contrary to our expectations, we did not find evidence for metabolic adaptation to colder environments based on our comparisons between northern and southern populations. We also found no evidence for an acclimation response of RMR to rearing temperature for three of the four pairwise comparisons examined. Understanding the thermal sensitivity of metabolic rate in gypsy moth, and understanding the potential for changes in physiology at range extremes, is critical for estimating continued spatial spread of this invasive species both under current and potential future climatic constraints.